Lamellar Macular Holes: The Role of Microperimetry in Functional Assessment. (14th April 2019) - Donati, Simone; Della Valle, Paola; Premi, Elias; Mazzola, Marco; Lo Presti, Laura; Azzolini, Claudio
Abstract : Introduction . The aim of our observational cross-sectional study was to evaluate the association between visual function and anatomical characteristics of LMH, considering in particular different subtypes of LMH and their features. Materials and Methods . This observational clinical study has been conducted in the Ophthalmology Clinic, ASST-Sette Laghi, University of Insubria of Varese-Como, Italy. Included patients underwent a complete ophthalmological examination, as well as MP1 microperimetry evaluation and optical coherence tomography (OCT). Two experienced masked observers evaluated OCT imaging in order to assess the integrity of the photoreceptor layer (interdigitation zone and ellipsoid zone: IZ/EZ) and the external limiting membrane (ELM). Results . Twenty-five patients affected by an LMH were evaluated. Eighteen eyes of 18 patients met the study criteria and were included. Based on morphological and functional data, LMHs were divided into two subgroups: tractional (tLMH) and degenerative (dLMH). We identified 11 tLMHs and seven dLMHs. Functional parameters showed a significative difference in visual acuity and retinal sensitivity between the two groups, respectively: (sample median and the interquartile range) 0.0 (0.0; 0.09) LogMAR vs 0.15 (0.09; 0.52) LogMAR and 16.2 (14.2; 17.7) dB vs 10.0 (7.5; 11.8) dB (p < 0.05 ). Fixation was predominantly central in 90.9% of tLMH vs 71.4% of dLMH and stable in 81.8% tLMH vs 42.9% dLMH, but the differences were not statistically significant. Tractional and degenerative LMHs showed no significant differences in central foveal thickness. Conversely, LMH depth and horizontal diameters appeared different between the two groups. Tractional LMH showed a greater depth 257 (205; 278) μ m vs 190 (169; 249) μ m, whereas degenerative LMH showed a greater horizontal diameter 653 (455; 750) μ m vs 429 (314; 620) μ m (p < 0.05 ). IZ/EZ line was unaffected in 81.8% of tLMHs eyes versus 14.3% of dLMHs eyes (p < 0.05 ). Visual acuity and retinal sensitivity were higher in eyes with integrity of both IZ/EZ and ELM compared to those with a disruption of one or both layers (p < 0.05 ). Conclusion . Two different subtypes of LMH showed peculiar functional aspects due to their morphological features. Tractional LMHs revealed higher visual acuity and retinal sensibility due to the relative preservation of the outer retinal layers compared to degenerative LMHs. Moreover, we underlined the importance of microperimetry to better identify functional defects in macular degenerative pathologies.